COMMUNITY STRUCTURE MACROZOOBENTHOS IN TANJUNG BUTON WATER’S IN SIAK DISTRICT RIAU PROVINCE - Yulina Sari; Aras Mulyadi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in March 2015 in Tanjung Buton water’s. This research aims to determine the content of organic matter in the sediment, sediment fractions, sediment grain size, the type and abundance of macrozoobenthos and relationship between the content of organic matter in sediment, macrozoobenthos abundance and sediment grain size. The method used in this research was survey method. Sample of sediment were collected from 3 stations. Sampling of macrozoobenthos was carried by using 1m x 1m plot. The analysis, identification and quantification were carried out in Marine Chemistry Laboratory and Marine Biology Laboratory, Faculty of Fisheries and Marine Science, University of Riau in Pekanbaru. The result showed that sediment organic content in Station 1 was 6,91%, Station 2 was 6,24% and Station 3 was 6,23%. The macrozoobenthos abundance varied from 11-32, ind/m2. Makrozoobenthos that were found in Tanjung Buton water’s composing of 4 classes of: gastropoda, bivalvia, polychaeta, merostomata. Diversity index (H’) was 1,74-2,34, dominance index (C) was 0,23-0,34 and uniformity index (E) was 0,36-0,37. Relationship between organic content in sediment and macrozoobenthos abundance in Tanjung Buton water’s were y = 58,61-6,060x, R2 = 0,113, r = 0,34. While relationship between sediment grain size and organic content in sediment in Tanjung Buton Waters were y = 11,20-0,823x, R2 = 0,081, r = 0,24.Key Words: Tanjung Buton, macrozoobenthos, community structure, sediment